Teaching Video NeuroImages: Hollenhorst plaque - Gonzalez-Castellon, Marco (Lippincott Williams & Wilkins, 2013)
A 73-year-old man with hypertension and hyperlipidemia was seen in clinic complaining of decreased vision in his right eye. Bedside examination demonstrated a right eye inferior lateral visual field defect due to ischemic optic neuropathy and 2 bright intraluminal yellow plaques located in 2 different arteriolar bifurcations (figure). Carotid ultrasound showed an unstable, mobile, nonocclusive, ulcerated plaque in the right carotid bifurcation (see video on the Neurology® Web site at www.neurology.org). Hollenhorst plaques(1) are cholesterol crystal emboli thought to originate from the ipsilateral carotid artery bifurcation that, in the absence of amaurosis fugax or stenosis, are not associated with an increased risk of ipsilateral cerebral infarct.(2)